Efficacy of Secondary Metabolites Produced by Bacillus Amyloliquefaciens on the Inhibition of Zymoseptoria Tritici (Global Journal of Science Frontier Research, 2020)
The strain I3 of Bacillus amyloliquefaciens, which was isolated from soft wheat leaves, has revealed, in vitro and in vivo, a high antagonistic potential against septoria leaf blotch of wheat. In order to investigate the existence of antifungal molecules secreted by strain I3, the filtrates of this strain were tested for their inhibitory activity on the germination of pycnidiospores of the two strains of Zymoseptoria tritici, G1-1 and A5-1 isolated from soft wheat and durum wheat, respectively. The antibiosis assays showed a high level of inhibitory activity, with inhibition rates ranging from 94% to 99% compared to the control after 96 hours of incubation. Filtrate analysis by high-performance liquid chromatography coupled to mass spectrometry (HPLC-MS), have identified several families of lipopeptides reported as antifungal molecules (iturins, fengycins, and surfactins); and polyketides (macrolactins, chlorotetaines, and bacillaenes) which would also be responsible for the antagonistic activity against Z. tritici.
Keywords: nephelometry; antibiosis; HPLC-MS; secondary metabolites; bacillus amyloliquefaciens I3; zymoseptoria tritici